Compare and evaluate the severity of alveolar bone loss in female patients with and without tobacco smoking in chronic Periodontitis- an observational study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The 1996 World Workshop in Periodontics looked at a variety of research and found that smoking was associated withan overall increased risk of severe periodontal disease, with an estimated overall odds ratio of 2.82.5 Previously, researchers had linkedsmokers; higher frequency and severity of periodontal disease to the presence of more plaque and calculus than non-smokers. However,research shows that the effect of smoking on periodontal condition is independent of the plaque index and dental cleanliness of theindividual, thanks to a greater knowledge of the host response. To the best of our knowledge, this is the first study of its kind to beconducted. Scarce research is seen regarding relationship of smoking females with periodontitis. The hypothesis of our study was thatthere is a significant association between tobacco cigarette smoking and periodontitis among female population. As a result, smokingappears to have a direct effect on periodontal tissues. Periodontitis is an inflammatory condition of the teeth’s supporting tissues causedby various microorganism that leads to the gradual deterioration of the periodontal ligament and alveolar bone, resulting in pocketformation, recession, or both . Smoking habits is prevalent in female gender extensively in this part of the country. Hence, this studywas undertaken to analyse the clinical and radiological alterations in smokers and non- smokers female population to further strengthenour knowledge on etiopathogenesis of periodontal disease with effect modified by gender.Materials and Method 60 female patients in the age group of 25 – 50 years, with moderate to severe form of chronic Periodontitis, weredivided into 2 groups- Group A-Female patients with tobacco smoking and Group B -Female patients without tobacco smoking.Results The result vary significantly in both the groups. In female smokers , molars were the gravely affected teeth in both maxillaryand mandibular arches while the canines were the least affected and Palatal surface showed a greater bone loss in both upper and lowerarches.Conclusion: In this study we have concluded that Bone loss higher in smoking population than their non-smoking cohorts. Maxillarymolars had a higher amount of bone loss appreciated radiographically followed by maxillary incisors, premolars and canines. The samefindings were true for mandibular molars. Maxillary palatal and mandibular lingual exhibited greater bone loss scores than buccalsurfaces. We strongly recommend a prospective cohort study of cigarette smoking in females and its relation with periodontal diseasein future research. All the periodontal parameters including gingival index, CAL , Plaque index significantly higher in female smokersas compared to non smokers